O dynamice i opozycjach XIX-wiecznej kultury: Recenzja książki Sabiny Brzozowskiej [2018] pt. W zwierciadle idei. Literatura Młodej Polski – konteksty. - Sobieraj, Tomasz (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
Sabina Brzozowska’s monograph consists of a coherent collection of comparative and historical and literary studies of various artistic and ideological aspects found in selected works of Polish and European modernism. The author focuses on the dramas by Stanisław Wyspiański, Stanisław Przybyszewski, Tadeusz Rittner, Tadeusz Miciński and on the prose by Wacław Berent, Miciński and Thomas Mann. The interpretations of the works included in the monograph show a common area of European nineteenth-century culture, especially of the modernist period. Brzozowska’s reading experience focused on uncovering the intertextual and comparative relationships between, for instance, Wyspiański’s Wesele (The Wedding) and Mann’s Buddenbrooks, Berent’s Ozimina (Snow Crop) and Czarodziejska Góra (The Magic Mountain), Rittner and Ibsen. High art literature of the modernist period found its counterpoint in popular culture, including the new media. The author reconstructed this development dynamic of modernist culture in multiple versions.